Exploring Involuntary Executive Turnover Through A Managerial Discretion Framework - Shen, Wei; Cho, Theresa S. (Academy of Management Review, 2005)
We develop a theoretical framework of involuntary executive turnover by paying close attention to the environmental and organizational contexts executives face. We classify these contexts into four scenarios based on high and low levels of latitude of objectives and latitude of actions. Our framework posits that latitude of objectives and latitude of actions interact to affect the causes and performance consequences of involuntary executive turnover, as well as which executives will be forced to depart.